2013
DOI: 10.1182/blood-2012-10-455055
|View full text |Cite
|
Sign up to set email alerts
|

Forssman expression on human erythrocytes: biochemical and genetic evidence of a new histo-blood group system

Abstract: Key Points• A new histo-blood group system was discovered, based on the identification of Forssman glycolipid antigen on human red blood cells.• A newly described polymorphism in the GBGT1 gene activates the encoded enzyme to synthesize Forssman antigen. IntroductionCarbohydrate histo-blood group antigens, first recognized on red blood cells (RBCs) in 1900, 1 have been suggested to be part of our innate immune response. 2 Major carbohydrate histo-blood groups in man include the ABO, P1PK, H, Lewis, I, and GLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(124 citation statements)
references
References 38 publications
1
122
0
1
Order By: Relevance
“…This survival correlation further validates anti-Fs di responses as a potential biomarker for PROSTVAC-VF and extends its clinical significance from mCRPC patients receiving PROSTVAC-VF as a single agent to include patients with radiographically evident metastases receiving combination therapy. (32,33). Third, the chicken embryo dermal cells used as host cells for production of the poxviruses express blood group A (34) and the Forssman antigen (35,36).…”
Section: Anti-fs DImentioning
confidence: 99%
“…This survival correlation further validates anti-Fs di responses as a potential biomarker for PROSTVAC-VF and extends its clinical significance from mCRPC patients receiving PROSTVAC-VF as a single agent to include patients with radiographically evident metastases receiving combination therapy. (32,33). Third, the chicken embryo dermal cells used as host cells for production of the poxviruses express blood group A (34) and the Forssman antigen (35,36).…”
Section: Anti-fs DImentioning
confidence: 99%
“…The A pae positive family members showed a divergent Ab and lectin reaction pattern of the RBCs. The Helix pomatia lectin resulted in a strong reaction, polyclonal Ab anti-A gave a weak response and monoclonal Ab anti-A were nonreactive, thus presenting an apparent paradox [1,5].…”
Section: Historymentioning
confidence: 99%
“…Several years later a group of Swedish researchers showed that, Fs glycolipid, usually only found in the RBCs of non-primate mammals, was strongly expressed in human RBCs of the subgroup A pae [1].…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations